ANALISIS STRUKTURAL ANTOLOGI PUISI ALARM SUNYI KARYA EMI SUY - Maulida Laily Kusuma Wati; Mohammad Kanzunnudin; Irfai Fathurohman (Universitas Muria Kudus, 2022)
The purpose of this research are two (1) analysis the structural poetry of the anthology of Alarm Sunyi by Emi Suy.This type of research is descriptive qualitative. The research anthology method used in the research anthology of poetry Alarm Sunyi by Emi Suy is descriptive qualitative method. The object of this research is the poetry anthology book Alarm Sunyi by Emi Suy published by Taresi Jakarta 2018. The data analysis technique uses heuristic and hermeneutic reading methods. The theoretical framework of this research is the theory of (1) the types of poetry, (2) the meaning of poetry, (3) the structure of poetry, (4) the semiotic analysis of poetry. The theoretical framework for the types of poetry comes from Waluyo (1991). The theoretical framework for understanding poetry comes from Pradopo (2008), Kosasih (2015). The theoretical of poetry structure, Waluyo (2010), Teeuw (1984). The results of this study are two aspects (1) structural analysis of the poem Alarm Sunyi by Emi Suy.